RANCANG BANGUN SISTEM INFORMASI GEOGRAFIS (SIG) LOKASI PRAKTEK KERJA INDUSTRI (PRAKERIN) SMK METHODIST MEDAN BERBASIS WEB - Imam Rangga Bakti; Yola Permata Bunda; Cut Try Utari (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2021)
System Information Geographical (SIG) in one of based information system for storing, managing, and analzing, aw well as retrieving geograpchical referenced data that develope rapidly in the last five years.in this research, reseachers will build a geographical information system appllication for industrial work practice bby utilyzing location mapping to facilitate students in conducting and obtaining information about industrial work practices that is determined by SMK Methodist Medan. In the development of this system the research wil use some tods and programming languange such as Vscode as a text editor, PHP as programming language MySql as a database for data storage and googlemaps to help display map and live location in this research later student will easily get an information about industrial work practice at SMK Methodist Medan.